Experimental enhancement of tubular solar still performance using rotating cylinder, nanoparticles' coating, parabolic solar concentrator, and phase change material. (January 2022) - Essa, F.A.; Abdullah, A.S.; Alawee, Wissam H.; Alarjani, A.; Alqsair, Umar F.; Shanmugan, S.; Omara, Z.M.; Younes, M.M.
Abstract: It is known to us that the problem of freshwater shortage is constantly exacerbated by the rapid population increase and the great diversity of different industries that need water to continue their work. It is also well known that solar stills are one of the thermal solutions to this problem, but they are disadvantaged by their low productivity. So, this study presents an experimental study to improve the performance of the tubular solar still with rotating drum (TDSS) using nanoparticles' coating, parabolic solar concentrator (PSC), and phase change material (PCM). Different operating variables were tested in this study. This combination of using PSC and PCM is investigated for the first time in TDSS. PSC was used to concentrate the solar rays on the back side of the drum, which raised the evaporation rate. The nanoparticles coating was used to paint the surfaces of the drum and basin still to change the film-wise mechanism of water to drop-wise. In addition, the effect of various rotating speeds of drum on the performance of TDSS was investigated. The experimental results revealed that using the rotating cylinder inside the tubular solar still (TSS) increased the productivity of the distiller as compared to that of the conventional solar still (CSS). Furthermore, the TDSS with nanoparticles' coating provided a productivity of 6650 mL/m 2 .day compared to 2800 mL/m 2 .day for the CSS with an enhancement by 137%. Besides, the maximum increase in productivity of TDSS when using PSC and PCM was obtained at 0.3 rpm, where the productivity improvement was around 195% and 218%, respectively. The thermal efficiency of the CSS was around 32–34%. Highest thermal efficiency of the TDSS with PCM was 63.8% at 0.3 rpm. Also, the cost of distilled water of TDSS with nanoparticles' coating, PSC, and PCM is 0.024 /L compared to 0.029 /L for the CSS, and the payback time was around 5 and 3 months, respectively.